Pengaruh Penggunaan Teknik Think Talk Write (TTW) Terhadap Keterampilan Menulis Teks Eksplanasi Siswa Kelas XI MAN Sibolga - Joice Valentine Caniago; Yulianti Rasyid (Universitas Negeri Padang, 2023)
There are three purposes of this study, first, to describe the skills of writing explanatory texts for class XI MAN Sibolga before using the ttw technique. Second, describe the skills of writing explanatory texts of class XI students of MAN Sibolga after using the ttw technique on the writing skills of the eleventh grade students of MAN Sibolga. This type of research is quantitative research with experiment methods. This research design is a one group pretest- posttest design. The population in this study were all class XI students of MAN Sibolga who were registered in the 2022/2023 academic year with a total of 208 people spread over six classes. The sample of this research is the students of class XI IPS 2, totaling 35 people who are determined by purposive sampling technique. The data of this research is the score of the test results of the writing skill of the explanatory text before and after using the ttw technique, the students of class XI MAN Sibolga are in the qualification more than enough with an average score of 68,81. Second, the skill of writing an explanatory text after using the ttw technique, the students of class XI MAN Sibolga are in the very good qualification with an average value of 87,38. Third, based on the t-test, the research hypothesis H1 was accepted at a significant level of 95% and degrees of freedom (dk)= (n-1) because tcount > ttable (9,72 > 1,70). Based on the results of the study, it was concluded that the students explanatorytext writing skill in class XI MAN Sibolga after using the ttw technique were better than before using the ttw technique. Thus, the ttw technique could be applied as an alternative in learning explanatory text writing skills.